Energy intake, nonexercise physical activity, and weight loss in responders and nonresponders: The Midwest Exercise Trial 2. (August 2015) - Herrmann, Stephen D.; Willis, Erik A.; Honas, Jeffery J.; Lee, Jaehoon; Washburn, Richard A.; Donnelly, Joseph E.
<x xml:space="preserve">Abstract</x> Objective To compare energy intake, total daily energy expenditure (TDEE), nonexercise energy expenditure (NEEx), resting metabolic rate (RMR), nonexercise physical activity (NEPA), and sedentary time between participants with weight loss <5% (nonresponders) vs. ≥5% (responders) in response to exercise. Methods Adults (18‐30 years) with overweight/obesity (BMI 25‐40 kg/m2) were randomized to exercise: 5 days/week, 400 or 600 kcal/session, 10 months. Results Of the participants, 40 responded and 34 did not respond to the exercise protocol. Nonresponder energy intake was higher vs. responders, significant only in men (P=0.034). TDEE increased only in responders (P=0.001). NEEx increased in responders and decreased in nonresponders, significant only in men (P=0.045). There were no within‐ or between‐group differences for change in RMR. NEPA increased in responders and decreased in nonresponders (group‐by‐time interactions: total sample, P=0.049; men, P=0.016). Sedentary time decreased in both groups, significant only in men. Conclusions Men who did not lose weight in response to exercise (<5%) had higher energy intake and lower NEEx when compared with men losing ≥5%. No significant differences in any parameters assessed were observed between women who lost <5% vs. those losing ≥5%. Factors associated with the weight loss response to exercise in women warrant additional investigation.